Personal Income Tax and Domestic Debt Servicing: Verdict from Panel Fixed Effects - Adegbite, Tajudeen Adejare (Universitas Kristen Maranatha, 2024)
Purpose - This study examined the effect of PIT on domestic debt servicing in South western states, Nigeria. Design/methodology/approach - Data gathered from all south western states were analyzed with Pearson correlation, VIF, and panel data analytical tools such as pooled regression, fixed effects and random effects estimations. Hausman was further ignited to select a better model amid fixed effects and random effects estimations. Other tests such as autocorrelation test, VIF, and heteroscedasticity were also conducted. Findings - It was divulged from the study that PAYE was discovered having positive effect on domestic debts servicing. Direct assessment and road tax also possessed cordial relationships with domestic debt servicing but other taxes impacted domestic debt servicing negatively. Conclusively, positive correlation was established between personal income tax revenue and domestic debt servicing in South-Western Nigeria. Also, PIT has positive, significant and statistical impact on domestic debt servicing in South-Western Nigeria. When personal income tax collections increase, the government tends to rely less on domestic debt to finance its activities. Research limitations/implications – It is recommended that government should strengthen tax enforcement mechanisms to display proper accountability and transparency measures so that revenue realized from PIT will be enormously enough to emaciated domestic debt significantly in south western Nigeria. Government should also lessen domestic borrowings but activate unexploited taxes embedded in PIT, and curtail corruption in borrowed funds for effective usage in the country. Keywords: Domestic Debt Servicing, PIT, PAYE, Road Tax, Direct Assessment